Iron Complexes of Flavonoids-Antioxidant Capacity and Beyond - Kejík, Zdeněk; Kaplánek, Robert; Masařík, Michal; Babula, Petr; Matkowski, Adam; Filipenský, Petr; Veselá, Kateřina; Gburek, Jakub; Sýkora, David; Martásek, Pavel; Jakubek, Milan (International journal of molecular sciences, 2021)
Flavonoids are common plant natural products able to suppress ROS-related damage and alleviate oxidative stress. One of key mechanisms, involved in this phenomenon is chelation of transition metal ions. From a physiological perspective, iron is the most significant transition metal, because of its abundance in living organisms and ubiquitous involvement in redox processes. The chemical, pharmaceutical, and biological properties of flavonoids can be significantly affected by their interaction with transition metal ions, mainly iron. In this review, we explain the interaction of various flavonoid structures with Fe(II) and Fe(III) ions and critically discuss the influence of chelated ions on the flavonoid biochemical properties. In addition, specific biological effects of their iron metallocomplexes, such as the inhibition of iron-containing enzymes, have been included in this review.
Keywords: flavonoidy; Animals; Antioxidants; hem; metallocomplexes; železo; Flavonoids; vazba proteinů; Molecular Structure; Structure-Activity Relationship; lidé; komplexní sloučeniny; flavonoids; Coordination Complexes; molekulární struktura; Heme; Iron; chelátory; antioxidancia; ionty; Chelating Agents; vztahy mezi strukturou a aktivitou; Ions; zvířata; Protein Binding; iron ions; Humans